Phorbas topsenti and Phorbas tailliezi (Demospongiae, Poecilosclerida), new names for the Mediterranean ‘Phorbas paupertas' and ‘Phorbas coriaceus'. - Vacelet, J.; Pérez, T. (Zootaxa, 2008)
A common Mediterranean species of Phorbas has been frequently identified under the specific name paupertas, referring to the sponge described as Hymeniacidon paupertas by Bowerbank 1866 from the north coasts of Europe. It is actually different from this species, and a new name, Phorbas topsenti sp.nov., is proposed. A description of the morphology, spicule complement and cytology is given. Another Mediterranean species of Phorbas, Phorbas tailliezi sp. nov. is described.